Writing Europe - Ursula Keller (Central European University Press, 2003)
Democracy thrives on social dialogue and collective search for solution. As a forum for new ideas and impulses the Körber-Foundation seeks with its projects to involve citizens actively in social discourses. The private, non-profit-making foundation provides a forum for involvement in politics, education, science and international communication. Citizens who take part in competitions and round table discussions organized by the foundation benefit in many ways: they can pass on knowledge, iden...